Antibacterial Properties of Grape Seed Extract-Enriched Cellulose Hydrogels for Potential Dental Application: In Vitro Assay, Cytocompatibility, and Biocompatibility - Tovar Carrillo, Karla Lizette (2024)
Hydrogels elaborated from Dasylirion spp. and enriched with grape seed extract (GSE) were investigated for tentative use in dental treatment. Cellulose-GSE hydrogels were elaborated with varying GSE contents from 10 to 50 wt%. The mechanical and physical properties, antimicrobial effect, biocompatibility, and in vitro cytotoxicity were studied. In all the cases, the presence of GSE affects the hydrogel’s mechanical properties. The elongation decreased from 12.67 mm for the hydrogel without GSE to 6.33 mm for the hydrogel with the highest GSE content. The tensile strength decrease was from 52.33 N/mm2 (for the samples without GSE) and went to 40 N/mm2 for the highest GSE content. Despite the adverse effects, hydrogels possess suitable properties for manipulation. In addition, all hydrogels exhibited excellent biocompatibility and no cytotoxicity, and the antibacterial performance was demonstrated against S. mutans, E. Faecalis, S. aureus, and P. aureginosa. Furthermore, the hydrogels with 30 wt% GSE inhibited more than 90% of the bacterial growth.